Increasing levels of cornmeal improve chemical and fermentation parameters of maniçoba silage - Silva, Pedro Henrique Ferreira da (2024)
Ensiling maniçoba (Manihot pseudoglaziovii) is essential to preserve the nutrients of this forage plant. However, the plant moisture content may generate undesirable fermentations. The objective of this study was to evaluate the effects of different cornmeal inclusion levels (0%, 10%, 20%, and 30%) on the chemical composition and fermentation parameters of maniçoba silage, in addition to identifying the variables most affected by cornmeal. The concentrations of dry matter (DM), non-fiber carbohydrates (NFC), total digestible nutrients (TDN), and propionic acid increased with cornmeal inclusion levels (P < 0.05). Crude protein (CP), lignin, and butyric acid contents, as well as pH, were reduced by the additive (P < 0.05). Principal component analysis resulted in two main groups. Group I was formed by variables positively affected by cornmeal inclusion, namely DM, hemicellulose, NFC, and TDN. Group II contained variables that were negatively affected by cornmeal, namely CP, lignin, mineral matter, and butyric acid. Regardless of the addition of cornmeal, maniçoba silage displays an adequate chemical composition and a good fermentation profile for ruminant feeding. Dry matter and total digestible nutrients are the chemical variables most influenced by cornmeal inclusion, whereas pH and butyric acid are the fermentative parameters most affected by the moisture-absorbent additive. Including moderate levels of cornmeal in maniçoba silage is recommended to achieve the best fermentation profile and the highest concentration of digestible nutrients without mischaracterizing it as a roughage feed.